Structural and Chronological Evidence for the India-Eurasia Collision of the Early Paleocene in the Eastern Himalayan Syntaxis, Namjagbarwa - Jinjiang, ZHANG; Jianqing, JI; Dalai, ZHONG; Haiqing, SANG; Shundong, HE (Acta geologica Sinica (Beijing), 2002)
The eastern Himalayan syntaxis in Namjagbarwa is a high-grade metamorphic terrain formed by theIndia-Eurasia collision and northward indentation of the Indian continent into Asia. Right- and left-lateral slip zoneswere formed by the indentation on the eastern and western boundaries of the syntaxis respectively. TheDongjug-Mainling fault zone is the main shear zone on the western boundary. This fault zone is a left-lateral slip beltwith a large component of thrusting. The kinematics of the fault is consistent with the shortening within the syntaxis, andthe slipping history along it represents the indenting process of the syntaxis. The Ar-Ar chronological study shows thatthe age of the early deformation in the Dongjug-Mainling fault zone ranges from 62 to 59 Ma. This evidences that theIndia-Eurasia collision occurred in the early Paleocene in the eastern Himalayan syntaxis.